A spreadsheet for partitional calorimetry - Atkins, K.; Thompson , M. (Sportscience, 2000)
Partitional calorimetry is the measurement of heat storage in the body and the components of heat exchange (conductive, convective, radiative, and evaporative) between the body and the environment. We present here a spreadsheet using the principles of partitional calorimetry to estimate how a given environmental condition and/or clothing ensemble affects the ability of the body to gain or lose heat during prolonged exercise.